(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
The advancement of Information and Communication Technology (ICT) necessitates technology integration in modern education, particularly through innovations like the virtual laboratory. This solution addresses the practical challenge faced by Christian Irene Senior High School (SMA Kristen Irene) in Manado, where limited physical laboratory facilities hinder effective science learning and practical experience. Virtual laboratories offer safe, interactive, and constraint-free simulations, aligning with current technology-based curriculum demands. This activity aimed to introduce and implement virtual laboratory applications among teachers, facilitating their integration into the learning process. The expected outcome is the creation of a more interactive and effective learning environment, ultimately enhancing student preparedness for the digital era.